Tool edge honing using shear jamming abrasive media. Issue 1 (2020) - Chan, Jason; Koshy, Philip
Abstract: Nature is replete with fascinating landscapes sculpted through interactions with moving fluids. Drawing inspiration from such, this research investigated intriguing mechanisms underlying the novel application of abrasive non-Newtonian media for rounding sharp edges of cutting tools. Through appropriate deformation, these media may be forced to correspond to rapid and reversible variations in viscosity that span several orders of magnitude, which render them particularly suited to this application. The innovative process is demonstrated to be uniquely capable of honing tools of a complex macrogeometry, generating edges that are symmetric/asymmetric and those that comprise a gradient in microgeometry along the edge length.